2011
DOI: 10.2105/ajph.2009.169631
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Infection Among Women Reporting Sexual Activity With Women Screened in Family Planning Clinics in the Pacific Northwest, 1997 to 2005

Abstract: Higher C trachomatis positivity among women reporting same-sex sexual behavior supports investigation into potential explanatory factors, including sexual behaviors, biological susceptibility, routine C trachomatis screening disparities, sexual identity disclosure, and sexual network assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 39 publications
1
50
1
3
Order By: Relevance
“…17,20,27,73 This may be due, in part, to their perceived low risk for contracting STIs, including HIV, 73 despite evidence demonstrating that some WSW may have higher STI rates than heterosexual women. 5,74 Up to one third of WSW participants had at least one STI in the studies we identified. 14,18,20 Although HIV prevalence among WSW in two small Chinese studies was 0%, 75 HIV prevalence is likely higher in many areas, especially in Sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…17,20,27,73 This may be due, in part, to their perceived low risk for contracting STIs, including HIV, 73 despite evidence demonstrating that some WSW may have higher STI rates than heterosexual women. 5,74 Up to one third of WSW participants had at least one STI in the studies we identified. 14,18,20 Although HIV prevalence among WSW in two small Chinese studies was 0%, 75 HIV prevalence is likely higher in many areas, especially in Sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 98%
“…2 Contrary to this perception, research suggests that WSW engage in high-risk sexual behavior with both male and female partners. [3][4][5] In addition, recent data indicate that female-to-female sexual contact can transmit STIs such as human papillomavirus, 6 genital herpes, 7 and syphilis. 8 In March 2014, the U.S. Centers for Disease Control and Prevention (CDC) reported the first confirmed case of HIV transmission by female-to-female sexual contact.…”
Section: Introductionmentioning
confidence: 99%
“…[39]. The authors concluded that until more data are available to clarify the epidemiology of and risks associated with this common infection, WSW should undergo routine age-based screening for C. trachomatis as recommended for heterosexual women.…”
Section: Chlamydia Trachomatis and Neisseria Gonorrhoeaementioning
confidence: 99%
“…The common clinical manifestations of this infection include cervicitis, pelvic inflammatory disease and tubal factor infertility (Singh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%